2016
DOI: 10.3402/tellusb.v68.32803
|View full text |Cite
|
Sign up to set email alerts
|

Currents and convection cause enhanced gas exchange in the ice–water boundary layer

Abstract: A B S T R A C TThe presence of sea ice acts as a physical barrier for airÁsea exchange. On the other hand it creates additional turbulence due to current shear and convection during ice formation. We present results from a laboratory study that demonstrate how shear and convection in the iceÁocean boundary layer can lead to significant gas exchange. In the absence of wind, water currents beneath the ice of 0.23 m s(1 produced a gas transfer velocity (k) of 2.8 m d(1 , equivalent to k produced by a wind speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The results of Loose et al . [] also support this observation. However, the mathematical implication of equation that as normalf0, k must be bounded by an upper limit.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Loose et al . [] also support this observation. However, the mathematical implication of equation that as normalf0, k must be bounded by an upper limit.…”
Section: Resultsmentioning
confidence: 99%
“…The ice was likely melting even at the beginning of the time-series since the surface water temperature was always above the freezing temperature of water ( Figure 3). Changes in surface ice cover and total ice volume are both important factors during the study; changes in ice volume/thickness will affect 15 stratification and convection in the mixed layer as well as light penetration through the ice, and the surface ice cover affects the rate of gas exchange (Smith and Morison, 1993;Butterworth and Miller, 2016;Loose et al, 2016) CTD profiles at Little Narrows channel near the water pump intake showed substantial changes in stratification during the time-series (Figure 3). From 25 March through 8 April the water column was strongly stratified and we estimated the mixed layer depth to average 0.8(0.3) m. During this period, it was often difficult to determine the exact mixed layer depth because 20 the mixed layer depth was similar to the length of the CTD and obtaining a stable CTD response so close to the surface was challenging.…”
Section: Hydrographymentioning
confidence: 99%
“…From the submersible pump, water flowed through flexible high-pressure PVC tubing submerged underwater 15 to a 3-port pressure-relief valve (on shore) and was then pumped along shore (∼50 m) to our sampling apparatus. The water passed through three 10" canister filters (100, 20, and 5 µm nominal pore size) and then into a sampling manifold containing valves for distributing water for measurement of O 2 /Ar (continuously, by mass spectrometry) and for discrete sampling.…”
Section: Setup At Little Narrowsmentioning
confidence: 99%
See 2 more Smart Citations